Analisa Produktivitas Tanaman Kelapa Sawit di Afdeling IV Kebun Baru PT Perkebunan Nusantara IV Regional VI - Fathan Hably Azya; Sri Murti Tarigan (Dinasti Research, 2026)
This study examines the productivity of oil palm plantations in Afdeling IV Kebun Baru, Langsa City, Aceh. Oil palm is an important plantation commodity in Indonesia that plays a significant role in the national economy, providing employment, and producing vegetable oil and alternative fuels. Plant productivity is influenced by several factors such as rainfall, temperature, land suitability, fertilization, pest attacks, and production labor. The study was conducted using a descriptive method with secondary data collection in Afdeling IV Kebun Baru PT. Perkebunan Nusantara IV Regional VI. The data analyzed included rainfall, plantation production, labor, fertilization, and land conditions in 2023–2025. The results showed that rainfall conditions in Afdeling IV were classified as unstable. 2025 had the highest rainfall of 2,237 mm with two dry months, while 2023 and 2024 experienced four dry months. Unstable rainfall causes a decrease in production because it affects the formation of fresh fruit bunches (FFB), harvesting activities, road conditions, and the quality of production results. Production data shows that production realization in several years did not reach the RKAP target, especially in 2025, which experienced the largest production decline. The 2010–2012 planting year had higher productivity and average bunch weight (AGBW) compared to the young planting year, but in general, AGBW decreased each year. In addition to climate factors, the decline in productivity was also influenced by attacks by long-tailed monkeys (Macaca fascicularis), which caused shrinkage of FFB and a decrease in AGBW. Controlled efforts have been carried out through the installation of traps, but the results have not been effective because the plantation location is directly adjacent to a forest area. Other factors affecting productivity are fertilization and production labor. Fertilization is carried out twice a year using Urea, Dolomite, MOP, TSP, and NPK Mutiara fertilizers according to the company's standard dosage. Meanwhile, the harvesting workforce in Afdeling IV numbered 20 people with a contract basis adjusted based on the planting year and average bunch weight of the plants. Overall, the study concluded that oil palm productivity in Afdeling IV Kebun Baru is influenced by environmental factors, particularly rainfall, pest infestation, fertilizer effectiveness, and labor. The results of this study indicate that efforts to increase oil palm productivity require management strategies that can adapt to changing climate conditions as well as the implementation of integrated and sustainable pest control.